The Effect of Green Packaging Perception on Green Customer Loyalty mediated by Green Customer Satisfaction on Avoskin Brand Cosmetic Products in Bandung City - Mahendra, Serina Hesti; Putra, Hariyadi Triwahyu (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This research seeks to empirically investigate the extent to which perceptions of environmentally friendly packaging affect consumer loyalty toward Avoskin cosmetic products. Green customer satisfaction is positioned as an intervening variable within the context of Bandung-based Generation Z students. The measurement instruments employed in this study demonstrated adequate levels of validity and reliability, thereby justifying their use in data collection. A total of 120 respondents, all of whom had previously purchased Avoskin products, constituted the sample. The analytical approach comprised both simple and multiple regression models, supplemented with a Sobel test to evaluate mediating effects. Findings indicate that perceptions of green packaging positively and significantly affect customer satisfaction and loyalty, with satisfaction also emerging as a significant predictor and mediator in this relationship. However, future research is advised to explore alternative constructs that may more directly drive green customer loyalty. This finding also opens up opportunities for future researchers to explore other concepts that directly affect green customer loyalty. This research offers practical benefits to Avoskin in designing a marketing strategy to enhance product quality and attract more consumers from Generation Z